ChemInform Abstract: Sodium Lauryl Sulfate‐Catalyzed Oxidative Chlorination of Aromatic Compounds. Issue 2 (9th January 2013) - Mahajan, Tanu; Kumar, Lalit; Dwivedi, K.; Agarwal, D. D.
Abstract Compared to established methods, the advantages of the new method are higher yields, excellent purity, and shorter reaction times.